Rousseau i Tocqueville: przeciwstawne wizje republikańskiego wychowania - Mirocha, Łukasz (Filozofia Publiczna i Edukacja Demokratyczna, 2021)
It is legitimate to speak about two philosophies of education as presented by Jean-Jacques Rousseau. The first of the philosophies was elucidated in Emil, or on Education and its aim was to provide principles governing the process of upbringing of the man. Philo-sophical grounds for the second one were comprised in The Social Contract, however description of the education itself is delivered by Considerations on the Government of Poland. This concept refers to the civic education, education of the political community mem-ber. Alexis de Tocqueville depicts vision of education that varies fundamentally from the both grounded in Rousseau’s writing. Toc-queville’s vision stays at odds with the philosophy given in Emil, because it concerns civic aspects of the education. It is also not com-pliant with the concept stemming from Considerations, due to the fact that it stresses the role of other than state subjects in the edu-cation. The article comments on all three concepts of education out-lined above and finally relates them to the concept of positive and negative liberty provided by Isaiah Berlin.